2003
DOI: 10.1007/s00132-003-0580-5
|View full text |Cite
|
Sign up to set email alerts
|

Allografts in der Rekonstruktion von kn�chernen Defekten bei prim�r malignen Knochentumoren

Abstract: Reconstruction of large bone defects due to resection of musculoskeletal tumors can be performed with various types of massive homologous allografts. In combination with endoprostheses (composite allografts), various types of osteosyntheses, or autogenous vascularized grafts (most often the fibula), individual adaptation with respect to location, stability, and function is possible. In the elderly most often reconstruction with massive endoprostheses is performed; however, in younger patients limb-saving proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…Therefore mantle grafts are frequently used in the lower extremity [3436] but require a bone bank for matching allografts. Postoperative complications include fractures, nonunions, and infections [2, 13–15, 36, 37]. Current available data show that mantle grafts provide a higher primary stability compared to bilateral fibular grafts [14, 15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore mantle grafts are frequently used in the lower extremity [3436] but require a bone bank for matching allografts. Postoperative complications include fractures, nonunions, and infections [2, 13–15, 36, 37]. Current available data show that mantle grafts provide a higher primary stability compared to bilateral fibular grafts [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% of patients can receive limb-sparing resection [1–4] without having an increased risk of local recurrence. The spectrum of reconstruction possibilities is extensive with options as tumor arthroplasty [3, 57], massive allografts [813], mantle grafts (massive allograft combined with a vascularized fibular graft [2, 14, 15] or irradiated autograft combined with a vascularized fibular graft [1618]), and biological methods such as fibular grafts (vascularized/nonvascularized, unilateral/bilateral, “double barrel fibula”) [4, 1928], tibial flake, pelvis flake, and callus distraction [12, 29, 30]. …”
Section: Introductionmentioning
confidence: 99%
“…For instance these grafts have a lower technical demand for the surgeon and can reduce donor-site complications. 38,39 Several recent studies have shown that FNFAs harvested by a minimally invasive technique had the same benefits as FNFAs harvested by the periosteum-preserving technique in the treatment of bone defects in children and adults. [40][41][42] In the above-mentioned studies, complete regeneration of the donor site after FNFA harvesting was obtained in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…Common fillers include autogenous bone, allogeneic bone, artificial bone, artificial prosthesis, bone cement, etc. The author adopts autologous or cancellous allogenic bone and imported Austine replacement bone aiming at small bone defect; massive allogeneic bone is adopted aiming at big bone defect [ 1]; hemiarthrosis is adopted for cases with young age aiming at malignant tumor around knee joint, older cases undergo artificial prosthesis replacement [ 2]. Therefore, it can be concluded that allogeneic bone at least still occupy an important position in bone defect filler till present.…”
Section: Position Of Allogeneic Bone In Bone Defect Fillersmentioning
confidence: 99%